Seven types of meaning and seven attributes: a study of Chinese anti-pandemic neologisms under the dual perspective of lexical semantics and lexical pragmatics - Bo Yang (Penerbit Universiti Kebangsaan Malaysia, 2024)
From 2019 to 2023, a large number of neologisms related to the COVID-19 pandemic appeared in Chinese society, which has become a major linguistic phenomenon. Studying these neologisms can help to create new neologisms and use them more scientifically and rationally in times of major emergencies, avoid ambiguity and increase social influence and recognition. The authors identified 316 neologisms from the content published on Chinese government websites and media and networks that were collected as the research texts. First, we clarify the ways that neologisms are created and the neologism types from the perspective of lexicology. Leech's Seven Types of Meaning was used to analyse the basic composition of these neologisms. Combining this with the lexical pragmatics theory of the seven attributes of Lexicon proposed by Hou from a dynamic and three-dimensional perspective, the semantic situation of the neologisms in the context of the pandemic was analysed. The results show that most of the anti-pandemic neologisms conform to the seven types of meanings and seven attributes. A part of the neologisms has the deficiencies of unscientific word formation, discriminatory semantics, and infantilisation. In addition, there are two significant discoveries, the first of which is the four-level distribution of neologisms: cyber language, general spoken language, general written language, and elegant language. Secondly, it was found that there are two kinds of relationships between the parody words and the original words: lexical superposition and lexical distancing. Summarising and analysing these neologisms in the post-pandemic era has theoretical and practical value for contemporary language application and can provide linguistic insight into how agencies can respond to emergencies in the future.